Shaping suburbia how political institutions organize urban development - Lewis, Paul George 1966- (Univ. of Pittsburgh Press, 1996)
The American metropolis has been transformed over the past quarter century. Cities have turned inside out, with rapidly growing suburbs evolving into edge cities and technoburbs. But not all suburbs are alike. In Shaping Suburbia, Paul Lewis argues that a fundamental political logic underlies the patterns of suburban growth and argues that the key to understanding suburbia is to understand the local governments that control it - their number, functions, and power. Using innovative models and data analyses, Lewis shows that the relative political fragmentation of a metropolitan area plays a key part in shaping its suburbs.
Keywords: Administration locale - États-Unis; Banlieues - États-Unis; Design urbain - États-Unis; Stadsplanning; Stedelijk beleid; Urbanisatie; Urbanisation - États-Unis; Stadtplanung; Verstädterung; City planning -- United States; Local government -- United States; Suburbs -- United States; Urbanization -- United States; Stadtverwaltung; Vorort; USA